The Influence of Ketapang (Terminalia catappa) Bark Extract on Survival Rate and Histopathology of Common Carp (Cyprinus carpio) Liver Which is Infected by Aeromonas hydrophilia - Maftuch Maftuch; Gede Angga Krishna Fariestha; Heny Suprastyani (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
This research aims to investigate the influence of Ketapang (Terminalia catappa) bark extract (KBE) on the survival rate and liver histopathology of Common carp (Cyprinus carpio) which was Infected by Aeromonas hydrophilia. Experimental design with Completely Randomized Design (CRD). Obtained data were analyzed by using Analysis of Varian (ANOVA) and further Least Significant Differed (LSD) analysis. The main parameters in this research are the damage level of Common carp liver based on scoring value and survival rates. Based on the result from scoring data, it was shown that there is altered-histology on Common carp fish liver. The damages found were congestion, melanomacrofag, and necrosis. In average, treatment A (730 ppm) had the highest damage average while treatment C (770 ppm) had the lowest damage average value. The final result shows that the bigger the dose, the lower the damage. In contrast, the survival rates would decrease with the higher dose of KBE. It can be concluded that KBE able to reduce the liver alteration however in some extend it will cause the mortality.Keywords : common carp, histopathology, ketapang, liver, survival rate.